Islam in Global Modernity - Jung, Dietrich. author. aut Link
XI, 216 p. 1 illus.
Keywords: This book combines sociological theorising with studies on the Middle East and Islam. The diversity of modernities that can be observed in our world is linked to the claim of living in a global modernity, in a world society. The book underpins this claim with numerous excursions into Islamic history. It criticises the view that modernisation can be equated with westernisation and considers different projects of specifically Islamic modernities as integral parts of world society. From this perspective, the study contributes to the "provincialisation" of European history in contemporary social scientific thought. Contrary to the theories of postcolonialism associated with the call for the provincialisation of Europe, however, this book adheres to essential traditions of classical sociology. It thus aims to make a contribution to the social theoretical discussion on modernity, which is empirically underpinned with the help of data from the history of the Middle East and Islam. The author Dr Dietrich Jung is Professor in the Department of History and Director of the Center for Modern Middle East and Muslim Studies at the University of Southern Denmark (SDU) in Odense.